p53 - Ayed, Ayeda; Hupp, Theodore; SpringerLink (Online service) (Boston, MA : Springer US : Imprint: Springer, 2010)
This volume, p53, was developed primarily as a resource for access to key ideas in the field that have developed over the years including how transgenics have been used to study p53, how clinical genetics have identified and studied mutations in p53 found in human cancers, how p53 can be regulated by post-translational modification, and how key drug targets have been defined, namely MDM2, which has provided fundamental approaches for defining how p53 can be activated with potentially therapeutic effect. The key concepts in the chapters included provide a perspective on key paradigms in the p53 field.
TP53 Mutations in Human Cancers: Selection versus Mutagenesis -- Lessons on p53 from Mouse Models -- TP63, TP73: The Guardian$1 (Bs Elder Brothers -- The Regulation of p53 Protein Function by Phosphorylation -- The p53-Mdm2 Loop: A Critical Juncture of Stress Response -- Cooperation between MDM2 and MDMX in the Regulation of p53 -- Regulation and Function of the Original p53- Inducible p21 Gene -- p53 Localization -- Modes of p53 Interactions with DNA in the Chromatin Context -- p53$1 (Bs Dilemma in Transcription: Analysis by Microarrays -- Tumor Viruses and p53 -- p53 and Immunity.s
Keywords: Medicine; Oncology; Biomedicine; Cancer Research